The progress in the field of clinical staging for mental disorders within the last decade: an updated systematic review - Clarke, Sharon L.; Soons, Nicole; Videler, Arjan C.; van Alphen, Sebastiaan P. J.; Van, Henricus; Dil, Linda; Pappijn, Laurens; Corbeij, Sven; Broekhof, Beau; Chanen, Andrew M.; Hutsebaut, Joost (Frontiers in Psychiatry, 2025)
IntroductionClinical staging aims to refine psychiatric diagnosis by describing mental disorders on a continuum of disorder progression, with the pragmatic goal of improved treatment planning and outcome prediction. The first systematic review on this topic, published a decade ago, included 78 papers, and identified separate staging models for schizophrenia, unipolar depression, bipolar disorder, panic disorder, substance use disorder, anorexia, and bulimia nervosa. The current review updates this review by including new proposals for staging models and by systematically reviewing research based upon full or partial staging models since 2012.MethodsPsycINFO, MEDLINE, EMBASE, and the Cochrane databases were systematically searched from 2012 to June 2023. The original review’s eligibility criteria were used and extended with newly introduced categories of DSM-5 mental disorders, along with mental disorders for which a progressive course might be expected. Included papers: a) contained a complete or partial staging model, or b) focused upon clinical features that might be associated with stages, or c) focused upon treatment research associated with specific stages.ResultsSeventy-one publications met the inclusion criteria. They described staging models for schizophrenia and related psychoses (21 papers), bipolar (20), depressive (4), anxiety (2), obsessive-compulsive (3), trauma related (4), eating (3), personality disorders (2), and ‘transdiagnostic’ staging models (13).DiscussionThere is a steady but slow increase in interest in clinical staging and evidence for the validity of staging remains scarce. Staging models might need to be better tailored to the complexities of mental disorders to improve their clinical utility.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021291703.